Prevention of Mother-to-Child Transmission and the nurse's role: the case of a pregnant woman living with HIV in Bamenda Health District, in the North West Region of Cameroon - Nicoline Nsangli Ndong (Universidad Libre, 2024)
Prevention of Mother-to-Child Transmission (PMTCT) of HIV infection is a significant health problem facing most low and middle-income countries. Also known as Vertical Transmission, PMTCT refers to the interventions put in place to prevent the transmission of HIV from a mother living with HIV to her infant either during pregnancy, labor, delivery, or breastfeeding. In the absence of intervention, the rate of transmission of HIV from a mother living with HIV to her child during pregnancy, labor, delivery, or breastfeeding ranges from 15% to 45% (1). Approximately 1/3 of HIV-exposed babies will acquire HIV infection in the absence of preventive measures